THE ROLE OF POLITENESS AND IMPOLITENESS IN CHARACTER INTERACTIONS IN "ALL THE BRIGHT PLACES" NOVEL - Mappaita, S.S., M.Pd, Suci Pole; Setiawati, Nurul Sri; Arsyad, Muh Fahreza; Rudi, Muh Rendra Fahrezi (ELITERATE : Journal of English Linguistics and Literature Studies, 2025)
This study aims to analyze the role of politeness and impoliteness strategies in character interaction in the novel All the Bright Places by Jennifer Niven. The main issue addressed is how various forms of politeness and impoliteness are employed by the main characters and how these reflect their psychological states and social dynamics. This research applies a qualitative approach with a pragmatic analysis method, specifically drawing on Brown and Levinson’s politeness theory and Culpeper’s impoliteness framework. The data were taken from selected dialogues in the novel that illustrate expressions of polite and impolite language. The findings reveal that politeness tends to appear in conversations that express empathy, emotional support, and attempts to build closeness, while impoliteness is more prominent in contexts of internal conflict, psychological distress, or a desire for social distance. These language strategies play a crucial role in character development and reinforce the novel’s central themes of mental health and interpersonal relationships.